Rosja i Polska. Fragmenty historii miłosnej wrogości - Obirek, Stanisław (Humaniora. Czasopismo Internetowe, 2020)
The essay submitted is not purely scientific. The author is not a specialist in Polish-Russian relations, but is convinced that the analysis of relations with the eastern neighbor should not be left only to specialists. As a cultural anthropologist who has been dealing with the issues of collective memory for years, I am convinced that too little attention is paid by specialists to the mutual fascination of Russian and Polish cultures. Moreover, at present, the strongly Russophobic moods, in a significant part tof Polish society, influence the formation of too one-sided memory. Hence the political accents in the following text, which also does not avoid subjective accents. Needless to say, a possible polemic with the theses expressed by the author would be the best fulfillment of my expectations.